Increased Movement Of Healthy Living People (Germas) Through Physical Activity in Biih Village, Karang Intan District - Masdiputri, Rr. Sri; Ulfah, Bardiati; Sari, Bening Prawita (UrbanGreen Central Media, 2021)
Background: Indonesia still faces nutritional problems that have a serious impact on the quality of human resources (HR). Based on the results of Basic Health Research (Riskesdas) in 2013 that pregnant women's anemia is still 37.1%, babies with low birth weight 10.2%, toddlers with underweight 19.6%, and toddlers are overweight 11.8%. berbahasa inggris terdiri dari 150 kata dengan hanya 1 paragraf. It is not easy to instill a healthy lifestyle in the community where from the results of a survey of students who carry out community midwifery practices obtained data that most families in the village of Biih Karang Intan District do not know clearly how healthy behaviors where the community does not have a habit of doing light activities or sports, habits to monitor health regularly.Method: The method of implementing community service activities includes socialization to the Head of the village PKK team and kader for the implementation of community service activities regarding physical activity as a healthy community movement, namely gymnastics together. Results: The implementation of community service takes place in accordance with the planning that has been made. Gymnastics is carried out according to health standards. In the implementation went smoothly and the participants who attended were enthusiastic to follow gymnastics.